Diversity and Function of Phage Encoded Depolymerases - Knecht, Leandra E.; Veljkovic, Marjan; Fieseler, Lars (Frontiers in Microbiology, 2020)
Bacteriophages of the Podoviridae family often exhibit so-called depolymerases as structural components of the virion. These enzymes appear as tail spike proteins (TSPs). After specific binding to capsular polysaccharides (CPS), exopolysaccharides (EPS) or lipopolysaccharide (LPS) of the host bacteria, polysaccharide-repeating units are specifically cleaved. Finally, the phage reaches the last barrier, the cell wall, injects its DNA, and infects the cell. Recently, similar enzymes from bacteriophages of the Ackermannviridae, Myoviridae, and Siphoviridae families were also described. In this mini-review the diversity and function of phage encoded CPS-, EPS-, and LPS-degrading depolymerases is summarized. The function of the enzymes is described in terms of substrate specificity and applications in biotechnology.